WORKSHOP PENYUSUNAN BUSINESS PLAN PADA PONDOK PESANTREN ROJAUL HUDA YPI DARUN NASYA BANDUNG BARAT - Ismawati, Linna; Rukhviyanti, Novi; Putra, Kurniawan; Charisma Sasmita, Bella (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2023)
Darun Nasya Islamic Boarding School organizes Islam religious education supported by modern learning programs that equip students to have soft skills and hard skills in order to prepare students to enter the community. Darun Nasya provides entrepreneurial knowledge through implementation in the Saung Pondok Barokah Umat's business unit. The students participate in the management and development of the business unit as a means of entrepreneurial practice. The obstacles faced by Darun gas stations are learning media and business management knowledge that are still minimal, as well as difficulties developing business due to limited funds. Based on these problems, it is necessary to increase soft skill capacity through business plan preparation workshops so that Darun Nasya can develop its business units. Business Plan is a clear plan in running a business. Various benefits of preparing a Business Plan include clarity of business strategies and market opportunities, making business ideas and priorities, helping capital, and providing business information to investors and consumers. The implementation of a Business Plan preparation workshop can improve the skills of students in entrepreneurship.